Playground activities and gender variation in objectively measured physical activity intensity in Australian primary school children: a repeated measures study - Dean A. Dudley; Wayne G. Cotton; Louisa R. Peralta; Matthew Winslade (BMC, 2018)
Abstract Background Recent studies have sought to address the limited time for physical activity by focusing on increasing physical activity intensity among students during non-curricula periods and specifically school break times. We objectively measured the intensity of student physical activity (PA) during recess and lunch breaks at primary schools in the Western Sydney region of New South Wales (NSW), Australia using a 12-month repeated measures observation design study. Methods Systematic direct observation of recess and lunch breaks over a ten-week period in 2014 and 2015. 120 recess and lunch breaks across twenty schools (2014) with 839 periodic observations and across 15 schools with 587 periodic observations in 2015. Both observation periods were conducted over 10-weeks in Term 4 (September - December). Results The mean proportion of vigorous physical activity reported as a percentage (%VPA) across both time points was 16.6% (SD = 23.4). 36.8% (SD = 26.0) of time was spent walking and the remaining time (46.6%; SD = 30.4) was spent in sedentary activities. There was a significant decline in %VPA and increase in sedentary activity (p < 0.01) between the two time periods of measurement. In 2014, boys spent twice as much time in %VPA than girls during breaks in the school day and in 2015 this increased to nearly three times as much time in %VPA. %VPA also varied on the type of surface PA took place and the types of activities the children were allowed to undertake during breaks. Conclusions Recess and lunch breaks potentially offer an opportunity for children to participate in unstructured PA during the school day. Substantial variations in the %VPA during these periods exist. Addressing playground gender participation disparities and space usability/accessibility may be a necessary first step in promoting higher PA intensities during breaks.